Adaptive hard and tough mechanical response in single-crystal B1 VNx ceramics via control of anion vacancies. (15th June 2020) - Mei, A.B.; Kindlund, H.; Broitman, E.; Hultman, L.; Petrov, I.; Greene, J.E.; Sangiovanni, D.G.
Abstract: High hardness and toughness are generally considered mutually exclusive properties for single-crystal ceramics. Combining experiments and ab initio molecular dynamics (AIMD) atomistic simulations at room temperature, we demonstrate that both the hardness and toughness of single-crystal NaCl-structure VNx /MgO(001) thin films are simultaneously enhanced through the incorporation of anion vacancies. Nanoindentation results show that VN0.8, here considered as representative understoichiometric VNx system, is ≈20% harder, as well as more resistant to fracture than stoichiometric VN samples. AIMD modeling of VN and VN0.8 supercells subjected to [001] and [110] elongation reveal that the tensile strengths of the two materials are similar. Nevertheless, while the stoichiometric VN phase cleaves in a brittle manner at tensile yield points, the understoichiometric compound activates transformation-toughening mechanisms that dissipate accumulated stresses. AIMD simulations also show that VN0.8 exhibits an initially greater resistance to both { 110 } 〈 1 1 ¯ 0 〉 and { 111 } 〈 1 1 ¯ 0 〉 shear deformation than VN. However, for progressively increasing shear strains, the VN0.8 mechanical behavior gradually evolves from harder to more ductile than VN. The transition is mediated by anion vacancies, which facilitate { 110 } 〈 1 1 ¯ 0 〉 and { 111 } 〈 1 1 ¯ 0 〉 lattice slip by reducing activation shear stresses by as much as 35%. Electronic-structure analyses show that the two-regime hard/tough mechanical response of VN0.8 primarily stems from its intrinsic ability to transfer d electrons between 2nd-neighbor and 4th-neighbor (i.e., across vacancy sites) V–V metallic states. Our work offers a route for electronic-structure design of hard materials in which a plastic mechanical response is triggered with loading. Graphical abstract: Image, graphical abstract